(untitled) (Research, Society and Development, 2022)
The temporomandibular joint is a synovial joint with well-differentiated characteristics and functions, which has a cartilaginous disc placed between the mandibular head and the mandibular fossa of the temporal bone and which separates the temporomandibular joint into an upper and lower joint compartment. The superior articular compartment participates in mandibular translational movements while the inferior is involved in rotational movements. Temporomandibular disorders or TMDs form a set of signs and symptoms represented by an altered mandibular function and are defined as signs and symptoms characterized by pain and dysfunction in which anterior disc displacement without repositioning is just one of many disorders that may be present. Therefore, the present study aimed to determine all clinical aspects related to anterior displacement of the disc without repositioning and to verify its importance in the context of internal disorders of the temporomandibular joint. In the methodology, a documental study was carried out based on the periodic databases, Google Scholar and Scielo, whose time frame was between the years 2017 to 2022. In the results, initially it appears that the main characteristics of this disorder are the presence of pain intense and continuous, the presence of pain during any jaw movement and the difficulty to open the mouth. Regarding treatment, studies indicate that arthrocentesis and stabilizing bite plate are the most indicated.